Perilipins 2 and 3 lack a carboxy-terminal domain present in perilipin 1 involved in sequestering ABHD5 and suppressing basal lipolysis - Patel, Satish (National Academy of Sciences, 2014)
Lipid droplets (LDs) are a conserved feature of most organisms. Vertebrate adipocytes have evolved to efficiently store and release lipids for the whole organism from a single droplet. Perilipin 1, the most abundant lipid-coat protein in adipocytes, plays a key role in regulating lipolysis. In other tissues such as liver and muscle, LDs serve very different biological functions, buffering surplus lipids for subsequent oxidation or export. These tissues express perilipins 2 or 3, rather than perilipin 1. We sought to understand the role of perilipins 2 and 3 in regulating basal lipolysis. Bimolecular fluorescence complementation studies suggested that whereas perilipin 1 prevents the activation of adipose tissue triacylglycerol lipase by its coactivator, AB-hydrolase domain containing-5 (ABHD5), perilipins 2 and 3 do so less effectively. These differences are mediated by a conserved region within the carboxy terminus of perilipin 1 that binds and stabilizes ABHD5 by retarding its degradation by the proteosome. Chimeric proteins generated by fusing the carboxy terminus of perilipin 1 to the amino terminus of perilipins 2 or 3 stabilize ABHD5 and suppress basal lipolysis more effectively than WT perilipins 2 or 3. Furthermore, knockdown of perilipin 1 in adipocytes leads to replacement of perilipin 2 on LDs. In these cells we observed reduced ABHD5 expression and LD localization and a corresponding increase in basal lipolysis. Collectively these data suggest that whereas perilipin 1 potently suppresses basal lipolysis in adipocytes, perilipins 2 and 3 facilitate higher rates of basal lipolysis in other tissues where constitutive traffic of fatty acids via LDs is a necessary step in their metabolism.